An automatic artificial pancreas based on EHO-VPTIDF control algorithm. (30th June 2022) - Patra, Akshaya Kumar; Nanda, Anuja
The design of an elephant herding optimisation-variable parameter tilt integral derivative with filter (EHO-VPTIDF) controller for injecting the optimal dose of insulin through the artificial pancreases (AP) for blood glucose (BG) regulation in type I diabetes mellitus (TIDM) patients is presented in this manuscript. The EHO technique is used to optimise the controller parameters for better control execution in this strategy. MATLAB and Simulink are used to evaluate the EHO-VPTIDF controller's productivity in terms of accuracy, robustness and stability. The obtained results show that the EHO-VPTIDF controller is more effective at keeping blood sugar levels in the normal range (70-120 mg/dl). The relative result analysis with other well-known control techniques reveals the reason of improved control execution of the proposed controller.